2012
DOI: 10.1111/j.1365-313x.2012.04909.x
|View full text |Cite
|
Sign up to set email alerts
|

Potato CONSTANS is involved in photoperiodic tuberization in a graft‐transmissible manner

Abstract: CONSTANS (CO) is involved in the photoperiodic control of plant developmental processes, including flowering in several species and seasonal growth cessation and bud set in trees. It has been proposed that CO could also affect the day-length regulation of tuber induction in Solanum tuberosum (potato), a plant of great agricultural relevance. To address this question, we examined the role of CO in potato. A potato CO-like gene, StCO, was identified and found to be highly similar to a previously reported potato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 52 publications
4
118
1
Order By: Relevance
“…Together, our results show that the external coincidence photoperiod pathway that is known to control plant development, such as reproductive development, bud dormancy, and tuberization on a seasonal level (Böhlenius et al, 2006;González-Schain et al, 2012;Suárez-López et al, 2001) also regulates daily responses in Arabidopsis. It has been suggested that promoting stomatal opening and increasing photosynthesis (Ando et al, 2013) prior to flowering can be beneficial to plants; Figure 7.…”
Section: Discussion the Guard Cell Circadian System May Be Fine-tunedsupporting
confidence: 54%
“…Together, our results show that the external coincidence photoperiod pathway that is known to control plant development, such as reproductive development, bud dormancy, and tuberization on a seasonal level (Böhlenius et al, 2006;González-Schain et al, 2012;Suárez-López et al, 2001) also regulates daily responses in Arabidopsis. It has been suggested that promoting stomatal opening and increasing photosynthesis (Ando et al, 2013) prior to flowering can be beneficial to plants; Figure 7.…”
Section: Discussion the Guard Cell Circadian System May Be Fine-tunedsupporting
confidence: 54%
“…The diminishing of AGL20 might lead to inhibition of root elongation and induction of phase transition into storage stage (Achard et al 2007;Fleet and Sun 2005). In potato, common regulatory pathways and homologous genes (CO, SOC1 and FT) were conserved between the flowering and tuberization processes (González-Schain et al 2012;Rodriguez-Falcon et al 2006). IbMADS and AGL20-like (DV037991) were SR initiation factors that responded to CK, were involved in auxin-mediated initial thickening of the SR and were downregulated in SR (Ku et al 2008;McGregor 2006;Noh et al 2010;You et al 2003).…”
Section: Role Of Cytokinin In Suppression Of Agl20 and Ga Biosynthesismentioning
confidence: 98%
“…In a study on native CO genes of potato, StCO also functioned in a repressive manner in tuberization in potato (González-Schain et al, 2012). Overexpression lines of StCO tuberized later than wild-type plants, whereas silencing StCO expression promoted tuberization under both repressive and weakly inductive photoperiod conditions.…”
Section: Identification Of Cdf1 Alleles In Potatomentioning
confidence: 99%